Vigabatrin but not valproate prevents development of age-specific flexion seizures induced by N-methyl-D-aspartate (NMDA) in immature rats - Kubová, Hana; Mares, Pavel (Epilepsia, 2010)
In immature rats, N-methyl-D-aspartate (NMDA) induces several seizure types: flexion seizures (FS; in rats younger than 3 weeks), clonic seizures (in animals older than 3 weeks), and clonic-tonic seizures (CTS; in rats of all ages). FS represent a model of human infantile spasms. Effects of vigabatrin and valproate against all types of NMDA-induced seizures were studied in rats at postnatal days 12 (P12) and 25 (P25). NMDA (60 or 300 mg/kg) was injected to animals pretreated with vigabatrin (300-1,200 mg/kg; 24 h before NMDA) or valproate (100-400 mg/kg; 15 min before NMDA). Vigabatrin suppressed FS in P12 rats, but was ineffective against CTS in both age groups. Valproate suppressed CTS in P12, but not in P25 rats. Clonic seizures were rare in NMDA-treated P25 rats, but valproate pretreatment increased their incidence significantly. Neither drug decreased NMDA-induced mortality, which occurred within approximately 15 min after NMDA administration and reached almost 100% in all groups.
Keywords: Animals; novorozená zvířata; vigabatrin; Infant; Rats, Wistar; Seizures; epilepsie tonicko-klonická; Age Factors; N-Methylaspartate; Valproic Acid; Anticonvulsants; kyselina valproová; Animals, Newborn; věkové faktory; lidé; chování zvířat; křeče u dětí; antikonvulziva; N-methylaspartát; Receptors, N-Methyl-D-Aspartate; modely nemocí na zvířatech; kojenec; Disease Models, Animal; Epilepsy, Tonic-Clonic; krysa rodu Rattus; receptory N-methyl-D-aspartátu; Behavior, Animal; Vigabatrin; zvířata; Rats; Spasms, Infantile; záchvaty; potkani Wistar; Humans